Executive function developmental trajectories kindergarten to first grade: monolingual, bilingual and English language learners. Issue 3 (16th March 2022) - Castillo, Anabel; Khislavsky, Alexander; Altman, Meaghan; Gilger, Jeffrey W.
ABSTRACT: Many studies examine how bilinguals and monolinguals differ in their executive function abilities at one time-point or cross-sectionally. Fewer examine how these groups of children may differ over time. Using nationally representative data obtained from the Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011 (ECLS-K:2011), this study examines the developmental trajectories of executive functions among bilingual, monolingual and ELL (English Language Learner) children during their early school years across four time points from the start of kindergarten to the end of first grade while controlling for sex and socioeconomic status. Latent growth curve models show that ELL children start with lower executive function skills on the dimensional change card sort (DCCS) and Numbers Reversed. Yet, have a steeper slope on both tasks. Bilinguals also had a steeper slope on the DCCS Task despite not differing initially. In addition to cognitive assessments, we also evaluated teacher reports of children's executive function skills. Results from teacher reports showed that bilingual children have an initial higher perceived executive function in comparison to monolinguals. Together, the findings indicate that bilinguals and monolinguals are in some ways different in their cognitive control trajectories. Implications for findings regarding ELLs are further discussed.